2008
DOI: 10.1063/1.3009598
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of ultrafine-grain zirconium in the temperature range 4.2–300K

Abstract: The mechanical properties under uniaxial compression of cylindrical samples of ultrafine-grain (UFG) zirconium (grain size ∼0.4μm) obtained by intense plastic strain (IPS)—a combination of extrusion, annealing, and drawing—have been studied in the temperature range 4.2–300K. The mechanical characteristics of UFG zirconium have been studied in two structural states and the results are compared with each other as well as with the characteristics of coarse-grain polycrystals of this material (state 1—samples afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…In last years several methods of severe plastic deformation (SPD) were developed and used to produce nanomaterial with unique physical properties [2]. New ultrafine grained and nanostructured states of Zr were achieved recently by various SPD methods, such as a combination of extrusion, annealing and wire drawing [3], ECAP [4], and HPT [5,6]. It was shown that nanograined Zr has an improved strength characteristics, which sometimes is even accompanied by appropriate plasticity [3,6].…”
Section: Introductionmentioning
confidence: 99%
“…In last years several methods of severe plastic deformation (SPD) were developed and used to produce nanomaterial with unique physical properties [2]. New ultrafine grained and nanostructured states of Zr were achieved recently by various SPD methods, such as a combination of extrusion, annealing and wire drawing [3], ECAP [4], and HPT [5,6]. It was shown that nanograined Zr has an improved strength characteristics, which sometimes is even accompanied by appropriate plasticity [3,6].…”
Section: Introductionmentioning
confidence: 99%
“…The Young's modulus value was measured to be about 87.6 MPa, which validates the satisfactory calibration of the procedure since the accepted value in the literature is about 90 GPa. The experimental results for the o10 nm grain size specimens show remarkable size effect when compared to the literature [3], especially in terms of plastic strain. For about 300 nm grain size [3], the observed plastic strain of 15% overshadows our observation of only 1.5% strain for 410 nm grain size.…”
Section: Resultsmentioning
confidence: 66%
“…The experimental results for the o10 nm grain size specimens show remarkable size effect when compared to the literature [3], especially in terms of plastic strain. For about 300 nm grain size [3], the observed plastic strain of 15% overshadows our observation of only 1.5% strain for 410 nm grain size. Such size effect could also emanate from the specimen (bulk nanocrystal vs thin film nanocrystal), since thin films have orders of magnitude higher surface area compared to the bulk.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…Як було відзначено, на деформаційних кривих за температур, близьких до 4,2 К, спостерігається зміна виду пластичного плину від плавного до стрибкоподібного. Відзначимо, що низькотемпературна стрибкоподібна деформація характерна для багатьох ГЦКстопів (як грубозернистих, так і наноструктурних [27,29]).…”
Section: механічні властивостіunclassified